TRIP12 and UBR5 suppress spreading of chromatin ubiquitylation at damaged chromosomes - Gudjonsson, Thorkell; Altmeyer, Matthias; Savic, Velibor; Toledo, Luis; Dinant, Christoffel; Grøfte, Merete; Bartkova, Jirina; Poulsen, Maria; Oka, Yasuyoshi; Bekker-Jensen, Simon; Mailand, Niels; Neumann, Beate; et al. (Cell, 2012)
Histone ubiquitylation is a prominent response to DNA double-strand breaks (DSBs), but how these modifications are confined to DNA lesions is not understood. Here, we show that TRIP12 and UBR5, two HECT domain ubiquitin E3 ligases, control accumulation of RNF168, a rate-limiting component of a pathway that ubiquitylates histones after DNA breakage. We find that RNF168 can be saturated by increasing amounts of DSBs. Depletion of TRIP12 and UBR5 allows accumulation of RNF168 to supraphysiological levels, followed by massive spreading of ubiquitin conjugates and hyperaccumulation of ubiquitin-regulated genome caretakers such as 53BP1 and BRCA1. Thus, regulatory and proteolytic ubiquitylations are wired in a self-limiting circuit that promotes histone ubiquitylation near the DNA lesions but at the same time counteracts its excessive spreading to undamaged chromosomes. We provide evidence that this mechanism is vital for the homeostasis of ubiquitin-controlled events after DNA breakage and can be subverted during tumorigenesis.